2010
DOI: 10.1089/jwh.2009.1591
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy as a Barrier to Advancement for Women in Academic Medicine

Abstract: The hierarchical structure of academic medicine has a significant impact on faculty work experiences, including advancement, especially for women. We suggest that medical schools consider alternative models of leadership and managerial styles, including fixed terms for chairs with a greater emphasis on inclusion. This is a structural reform that could increase opportunities for advancement especially for women in academic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 24 publications
1
60
1
Order By: Relevance
“…11,12 Some studies suggest that academic medicine fails to provide support for both men and women faculty and that the current structures and economic environment are resulting in retention and promotion issues for all faculty. 13 However, research has shown that the hierarchical structure of academic medicine affects women more negatively than men, 14 as women traditionally thrive in a more egalitarian environment. In addition, the person at the top of the hierarchy is more frequently male, which can also affect women more negatively than men.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Some studies suggest that academic medicine fails to provide support for both men and women faculty and that the current structures and economic environment are resulting in retention and promotion issues for all faculty. 13 However, research has shown that the hierarchical structure of academic medicine affects women more negatively than men, 14 as women traditionally thrive in a more egalitarian environment. In addition, the person at the top of the hierarchy is more frequently male, which can also affect women more negatively than men.…”
Section: Discussionmentioning
confidence: 99%
“…45 55,56 and its impact on faculty in academic medical centers into focus, we planned a series of data-action cycles. In early LAN meetings, quotations, derived from the Interview Study [1][2][3][4][5][6]8 at the participating schools, were read aloud. In small rotating groups, each focusing on a theme in the qualitative data, LAN members discussed the meaning of these data.…”
Section: Methods Used At Meetingsmentioning
confidence: 99%
“…The deans of these schools agreed to participate personally in the LAN, and to have their faculty confidentially interviewed (Interview Study [1][2][3][4][5][6]8 ) and surveyed (National Faculty Survey 7,15,24 ). With instructions about the need for diversity in LAN membership, the dean of each participating school submitted a list of potential faculty members, from which the LAN Development Team selected 3 per school.…”
Section: School Selection and Lan Participantsmentioning
confidence: 99%
“…[5][6][7] In 2013-2014, women accounted for 47% of US medical students and one-third of all fulltime academic physicians. Emergency medicine (EM) was 1 of the top 10 specialties for women entering residency, with 38% of EM residency positions being filled by women.…”
Section: Introductionmentioning
confidence: 99%